A dynamic simulation of mangrove ecotourism management at the Lantebung of Makassar City. Issue 1 (October 2020) - Massiseng, A N A; Tuwo, A; Fachry, M E; Bahar, A
Abstract: Mangrove ecotourism is one of the important tourism in the coastal area. Mangrove ecosystems not only have physical and biological functions, but also have socioeconomic functions, including tourism potential. Utilization of mangrove areas to be ecotourism areas is an alternative that is very likely and high strategic, considering that ecotourism activities can encourage conservation of mangrove ecosystems as a buffer zone in coastal areas in particular. This study aims to formulate a model of mangrove ecotourism management in Lantebung of Makassar City. The study was conducted with a dynamic system approach with Powersim software (student version). The study location is at Lantebung of Makassar City, especially in mangrove area. Data collection, consist of; literature study, interviews and field observations. The results study obtained two dynamic model scenarios related to the management of the Lantebung mangrove eco-tourism, it's known that the optimal level of management that can be done now is to encourage better tourism promotion. This can be seen from the dynamic model results obtained that scenario-2 (the strategy to increase tourism promotion is 10%) is more optimal than scenario-1 (the strategy to increase community empowerment is 10%). Even though the aspect of mangrove conservation scenario-1 is better where it can increase the extent of existing mangroves (20 Ha) to 28.54 Ha or an increase about is 42.70%. Whereas the mangrove scenarios only increased to 25.25 Ha or increased about is 26.25% in the same period. While from the economic aspect, the scenario-2 is able to generate income from ecotourism of 620.25 million, and scenario-1 only produces 588.81 million in the next 30 years.